2001
DOI: 10.1016/s0002-9440(10)61691-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Gene Mutations and Frequent Use of VH1-69 and VH4-34 Segments in Hepatitis C Virus-Positive and Hepatitis C Virus-Negative Nodal Marginal Zone B-Cell Lymphoma

Abstract: Nodal marginal zone B-cell lymphoma (NMZL) is actually considered as a distinct entity that must be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 45 publications
6
101
0
1
Order By: Relevance
“…The first one is related to chronic antigenic stimulation with biological auto-immunity (RF and MC) leading to MZL [29,30], which as a result of secondary genetic events, may subsequently evolve towards transformed DLBCL. In de novo DLBCL we could hypothesise that a pro-tumour favourable environment can lead to B cell transformation [31] or that direct HCV infection of B cell may induce transformation [24].…”
Section: Discussionmentioning
confidence: 99%
“…The first one is related to chronic antigenic stimulation with biological auto-immunity (RF and MC) leading to MZL [29,30], which as a result of secondary genetic events, may subsequently evolve towards transformed DLBCL. In de novo DLBCL we could hypothesise that a pro-tumour favourable environment can lead to B cell transformation [31] or that direct HCV infection of B cell may induce transformation [24].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-HCV antibodies, the monoclonal compound of type II cryoglobulinemia and the lymphoma's immunoglobulins were found to be part of the same phenomenon, that is, the immunological response to HCV antigens. [21][22][23][24][25][26][27][28] Moreover, interaction between the virus and the cell surface activates STAT3 and leads to cellular transformation. 29 Finally, recent research showed that tumoral HCV-infected B cells have an increased rate of mutations of IgH, BCL-6, P53 and b-catenin.…”
Section: Introductionmentioning
confidence: 99%
“…Sequence analysis of the rearranged V H segments in these tumors revealed a substantial deviation from the germline V H 1-69 sequence with a degree of mutations very similar among the different cases of lymphoma [61].…”
Section: Shared Ighv1-69 Expression Among Different Lymphoproliferatimentioning
confidence: 87%
“…Six samples were kindly provided by Prof. Salvatore De Vita and Dr. Martina Fabris (Clinic of Rheumatology, DSMB, University of Udine, Italy), 10 by Dr. Valter Gattei (Clinical and Experimental Onco-Hematology Unit, Centro di Riferimento Oncologico, I.R.C.C.S., Aviano, PN, Italy), 6 by Dr. Massimo Di Nicola ("C. Gandini" Medical Oncology, Bone Marrow Transplantation Unit; Fondazione I.R.C.C.S., Istituto Nazionale per lo Studio e la Cura dei Tumori, National Cancer Institute, Milan, Italy), and 1 was collected at the Centro di Riferimento Oncologico, National Cancer Institute (I.R.C.C.S., Aviano, PN, Italy). IGHV1-69 expression was determined by sequencing of IGHV amplicons derived from either reversetranscribed total RNA or genomic DNA [28,61]. Buffy coats from 51 healthy donors were also collected and included in this study.…”
Section: Patients and Healthy Donorsmentioning
confidence: 99%
See 1 more Smart Citation